Prof. Ahmet Sözen's Exclusive Interview in BRT 35 Paralel - Sözen, Ahmet (BRT TV, 2014)
[Abstract Not Available]
Prof. Ahmet Sözen was interviewed by BRT's Yurdakul Cafer on the Cyprus problem and the regional developments. Sözen analyzes the current Cyprus peace negotiations, talks about the need for redesigning the Cyprus peace process and offers his model of redesigned peace process based on three pillars: (1) official peace negotiations; (2) a parallel track of CBMs (Confidence Building Measures); and (3) an unofficial regional dialogue on the peaceful exploitation of the hydrocarbon resources in the eastern Mediterranean.
Keywords: Cyprus Peace Negotiations; Cyprus Problem; Need for Redesigning the Cyprus Peace Process